Effectiveness of video enhancement on e-learning - Montazemi, Ali Reza; McMaster University, Michael G. DeGroote School of Business (My University, 2002)
Information technology can provide an effective and efficient learning environment, and as a result, life-long learning is now a reality. We are witnessing a growing use of e-Learning systems both as supports to traditional educational institutions and to corporations providing on-the-job training. The challenge is how to use information technology to improve the learning experience. This paper addresses the possible added value of video presentations in e-learning software. It shows, on the basis of empirical research, that students find a learning environment supported with video presentations more useful. Their intrinsic motivation to learn the subject matter had a significantly positive effect on their satisfaction with the availability of video presentations. Although our e-learning environment improved students' performance, video presentations had no significant effect on their performance on exams, however.
37 p. : ; Includes bibliographical references (p. 22-24). ; "October, 2002."
This research has been supported in part by grants from Indiana University Ameritech Fellow of Information Technology, and Natural Sciences and engineering Research Council of Canada.
Keywords: Computer-assisted instruction Education Higher > Computer-assisted instruction Management > Study and teaching (Graduate) > Case studies